Ethnomedicinal Knowledge on Water Purification in Selected Rural Areas of Ethiopia - Megersa, Moa; Beyene, Abebe; Ambelu, Argaw; Alebachew, Zeleke; Triest, Ludwig (Ethnobotany Research and Applications, 2015)
Plants have been used for water purification dating back to perhaps 2000 BC as noted in Egyptian inscriptions. Plant coagulants have the potential to serve as alternative water treatment agents especially in rural areas. Hence this study aimed to examine four promising plants and their uses as local coagulants for purification of turbid water in order to tackle rural quality water problems. Semi-structured interviews, focus group discussions, market surveys, and observation were used to gather information from three rural areas. Jar test experiments were carried out for treatment of high (209 NTU), medium (63 NTU), and low level (26 NTU) turbidity with the flocculent dosages of 0.03 g/L of powdered plant material. The four plant species used for treatment of turbid water were Maerua subcordata (Gilg) DeWolf, Moringa stenopetala (Baker f.) Cufod., Sansevieria ehrenbergii Schweinf. ex Baker, and Sansevieria forskaliana (Schult. & Schult.f.) Hepper & J.R.I.Wood. The finding shows that societies in each study area still depend on plant species for purification of turbid surface water. Coagulation tests revealed that tubers of M. subcordata and seeds of M. stenopetala were able to remove turbidity up to 97% at high turbidity levels and performance was better than leaves of S. ehrenbergii and S. forskaliana. Complementing traditional water treatment knowledge with coagulation tests and purification of the specific protein coagulant could help to identify appropriate solutions for rural people with difficulty preparing purified water.